Impact of limited English proficiency on presentation and clinical outcomes of patients undergoing primary percutaneous coronary intervention - Biswas, S.; Dinh, D.; Lucas, M.; Duffy, S.J.; Brennan, A.; Liew, D.; Cox, N.; Smith, K.; Andrew, E.; Nehme, Z.; Reid, Christopher; Lefkovits, J.; et al. (OXFORD UNIV PRESS, 2020)
Aims: To evaluate the association of limited English proficiency (LEP) with reperfusion times and outcomes in patients undergoing primary percutaneous coronary intervention (PPCI) for ST-elevation myocardial infarction (STEMI). Methods and results: This cohort study included 5385 patients who underwent PPCI in 2013-2017 and were prospectively enrolled in the Victorian Cardiac Outcomes Registry. Data linkage to government administrative datasets was performed to identify patients' preferred spoken language, socioeconomic status, and ambulance utilization data. Patients who had a preferred spoken language other than English were defined as having LEP. Of the study cohort, 430 patients (8.0%) had LEP. They had longer mean symptom-to-door time (STDT) [164 (95% confidence interval, CI 149-181) vs. 136 (95% CI 132-140) min, P < 0.001] but similar mean door-to-balloon time [79 (95% CI 72-87) vs. 76 (95% CI 74-78) min, P = 0.41]. They also had higher major adverse cardiovascular and cerebrovascular events (MACCE; 13.5% vs. 9.9%; P = 0.02), severe left ventricular dysfunction (11.0% vs. 8.4%, P = 0.02), and heart failure (HF) hospitalizations within 30 days of PPCI (5.1% vs. 2.0%, P < 0.001). On multivariable analysis, LEP did not independently predict 30-day MACCE [odds ratio (OR) 1.16, 95% CI 0.79-1.69; P = 0.45] but was an independent predictor of both prolonged STDT ≥ 120 min (OR 1.25, 95% CI 1.02-1.52; P = 0.03) and 30-day HF hospitalizations (OR 2.01, 95% CI 1.21-3.36; P = 0.008). Conclusion: Patients with LEP undergoing PPCI present later and are more likely to have HF readmissions within 30 days of percutaneous coronary intervention, but with similar short-term MACCE. More effort to provide education in varied languages on early presentation in STEMI is required.